High-Risk Features Are Prognostic in dMMR/MSI-H Stage II Colon Cancer - Mohamed, Amr; Jiang, Renjian; Philip, Philip A.; Diab, Maria; Behera, Madhusmita; Wu, Christina; Alese, Olatunji; Shaib, Walid L.; Gaines, Tyra M.; Balch, Glen G.; El-Rayes, Bassel F.; Akce, Mehmet (Frontiers in Oncology, 2021)
Background High-risk features, such as T4 disease, bowel obstruction, poorly/undifferentiated histology, lymphovascular, perineural invasion, and <12 lymph nodes sampled, indicate poor prognosis and define high-risk stage II disease in proficient mismatch repair stage II colon cancer (CC). The prognostic role of high-risk features in dMMR/MSI-H stage II CC is unknown. Similarly, the role of adjuvant therapy in high-risk stage II CC with dMMR/MSI-H (≥1 high-risk feature) has not been studied in prospective trials. The aim of this analysis of the National Cancer Database is to evaluate the prognostic value of high-risk features in stage II dMMR/MSI-H CC. Methods Univariate (UVA) and multivariate (MVA) Cox proportional hazards (Cox-PH) models were built to assess the association between clinical and demographic characteristics and overall survival. Kaplan–Meier survival curves were generated with log-rank tests to evaluate the association between adjuvant chemotherapy in high-risk and low-risk cohorts separately. Results A total of 2,293 stage II CC patients have dMMR/MSI-H; of those, 29.5% (n = 676) had high-risk features. The high-risk dMMR/MSI-H patients had worse overall survival [5-year survival and 95%CI, 73.2% (67.3–78.1%) vs. 80.3% (76.7–83.5%), p = 0.0001]. In patients with stage II dMMR/MSI-H CC, the high-risk features were associated with shorter overall survival (OS) along with male sex, positive carcinoembryonic antigen, Charlson–Deyo score >1, and older age. Adjuvant chemotherapy administration was associated with better OS, regardless of the high-risk features in dMMR/MSI-H (log-rank test, p = 0.001) or not (p = 0.0006). When stratified by age, the benefit of chemotherapy was evident only in patients age ≥65 with high-risk features. Conclusion High-risk features are prognostic in the setting of dMMR/MSI-H stage II CC. Adjuvant chemotherapy may improve survival specifically in patients ≥65 years and with high-risk features.